(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: To assess the nutritional status and related factors among esophageal cancer patients undergoing gastrostomy at K Hospital period 2024-2025. Subjects and methods: A cross-sectional study was conducted among 96 patients at K Hospital, Tan Trieu campus. Nutritional status was evaluated using PG-SGA, BMI, serum albumin, combined with clinical and laboratory parameters. Results: The prevalence of malnutrition according to PG-SGA was 81.25%, including 54.17% at moderate level (PG-SGA B) and 27.08% at severe level (PG-SGA C). Hypoalbuminemia (< 35 g/l) was found in 86.46% of patients. Based on BMI, 16.67% were undernourished, and 3.12% were overweight/obese. Patients over 70 years old, those with education below high school, living in rural areas, with comorbidities, dysphagia grade 2, and stage IV cancer have higher malnutrition prevalence in compare with other group. However, these factors were not statistically significant related. Conclusion: Malnutrition is common among esophageal cancer patients undergoing gastrostomy. Early nutritional screening and intervention are essential to improve patient condition, support treatment, and enhance outcomes.